Chest Pain Assessment and Imaging Practices for Nurse Practitioners in the Emergency Department. (January 2015) - Abid, Sidrah; Shuaib, Waqas; Ali, Shehzad; Evans, Dian Dowling; Khan, Muhammad Shahzeb; Edalat, Faramarz; Khan, Muhammad Jalal
Abstract : Chest pain is among the most common presentations in emergency departments worldwide, where a timely diagnosis and proper initial management is challenging but essential for health care providers. This article reviews the diagnostic workup of varying clinical presentations of adult chest pain with a focus on appropriate imaging practices based on current guidelines for risk stratification and care management that can guide the triage and medical decisions of nurses working in emergency and urgent care settings.